KEANEKARAGAMAN MAKROZOOBENTOS PADA EKOSISTEM TERUMBU KARANG DI PERAIRAN NGIARVARAT, MALUKU TENGGARA - Letsoin, Sahdan; Natan, Yuliana; Limmon, Gino V; Pattikawa, Jesaja A (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2026)
Coral reefs are marine ecosystems characterized by high biodiversity and play a vital role in the survival of marine biota. Among the organisms inhabiting this ecosystem are benthic fauna or macrozoobenthos, which occupy the substrate of the water body. This study aims to analyze the community structure of macrozoobenthos within the coral reef ecosystem of Ngiarvarat waters, Southeast Maluku. The research was conducted in August 2025 across eight transects, employing the Line Intercept Transect (LIT) method to measure coral cover and quadratic linear transects for macrozoobenthos data collection. Data analysis included the percentage of coral cover and community structure parameters, such as species density and ecological indices (diversity, evenness, and dominance). The results showed that the live coral cover percentage ranged from 63.0% to 89.8%, falling into the